The Income Adequacy of Provincial Social Assistance Payments to Non-Institutionalized Disabled Adults: Continuing Evidence Why Canada Needs a Guaranteed Annual Income Policy - Csiernik, Rick; Csiernik, Benjamin; Brideau, Melissa (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
An analysis of social assistance programs for non-institutionalized disabled adults found inconsistent income levels being provided between provinces. In less than half of the four family constructions created, a single disabled person, a married couple both disabled, a single parent with two children and a married couple, one disabled, one care taking and two children, did income exceed the Statistics Canada Low-Income Cut-Off. The majority of these instances arose because of the additional federal child support payments provided to families with children, a new initiative aimed at attempting to eliminate childhood poverty in Canada. The analysis also found that the larger the community the greater the likelihood of the disabled individual living in poverty. While improvements have occurred in some jurisdictions overall being disabled and unable to work equates to living in poverty in Canada. This analysis of income supports for this vulnerable populations contributes to the growing support for the development of a guaranteed annual income in Canada.